Domestic science--its influence in the home - Berkey, Charlotte Almira (My University, 1900)
Introduction: In all achievements we have our ideals. We try to bend every effort toward making that ideal complete. While broad culture is a beautiful thing, it is those who put their whole life into one subject, one intense purpose, that become the running gears in the cycle of life. Though designated by the homely name, Domestic Science, this subject stands for the highest calling of woman. It is as broad as the world and as deep as life itself. Scarcely a generation ago, Domestic Science first started in America, in the city of Boston. It took its start from the public school work, and this was first conducted under the auspices of the Young Women's Christian Association. Its success led its acknowledgment as an important factor in education. Domestic Science found its first departments in the agricultural colleges, and Kansas is distinguished as the first state to place it among her sciences.
Citation: Berkey, Charlotte Almira. Domestic science--its influence in the home. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Domestic science; Home economics; Nutrition; Theses; Manuscripts (documents)